Effect size catfish (pangasius pangasius) on resistance and speed pool for fisheries development capture - Rahmat, Nafira; ', Nofrizal; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The purpose of this research is to know the characteristic of catfish based on it’s size, age and the ability of swimming. The special purpose is to know and examine the swimming durance, swimming speed, maximum swimming speed and prolonged swimming speed of catfish that will be compared with the review of literature through this experiment method. The result of this experiment shows that the swimming durance, swimming speed, the maximum swimming speed and prolonged swimming speed of catfish will be weak in the certain speed when it is given the high stream flow.Keywords : Endurance, swimming speed, maximum swimming speed, and prolonged swimming speed of catfish.